0526 Monitoring Of Long Term Compliance Of Positive Airway Pressure By A Dedicated Sleep Team In Patients With Obstructive Sleep Apnea. (27th April 2018) - Singhi, S; Sullivan, S; Singhi, R
Abstract: Introduction: Positive Airway Pressure (PAP) is an effective treatment for obstructive sleep apnea (OSA). However, long term compliance remains a significant challenge in clinical practice with the national long-term compliance with PAP machine ranging from 30 to 70%. Centers consisting of a dedicated sleep team based approach versus the traditional non-dedicated sleep team physician clinic approach needs to be investigated and is the basis of our research. Our study is over eighteen months and consists of 1, 259 patients with an established diagnosis of OSA who were followed for their compliance in a dedicated sleep team approach. Methods: A prospective study that composed of 1, 259 patients with a history of obesity (BMI> 30kg/m2) and a diagnosis of moderate to severe OSA based on apnea hypopnea index >15. After the initiation of PAP therapy the patients were followed by a dedicated sleep team: 1. Patient Coordinator​ 2. Sleep Technologist (Certified Polysomnographic Technician—CPSGT) 3. Registered Nurse 4. Registered Polysomnography Technician (Registered Polysomnographic Technologist—RPSGT) 5. Sleep Medicine Board Certified Physician. Patients were followed at 1 week and at 3, 6, 12, and 18-month interval. PAP data was downloaded at each visit and analyzed. Results: Our results showed that 1, 007 patients (78%) were compliant with PAP therapy at the 18-month interval. The compliance criteria were defined as a minimum use of 70% over a 12-month period and greater than 4 hours use per night. Our significant results suggest that improved compliance was associated with multi-tiered educational approach. Conclusion: Many patients with OSA do not initiate or abandon therapy with PAP. Our results show that initial patient experience with PAP plays an important determining factor in regard to long term compliance. Biofeedback and patient-centered education along with professional support in such individuals is needed. Support (If Any): none.